Role of Web 2.0 in Scholarly Communication: A Survey of Select Indian Institutes of Management (IIMs) in India - Singh, Malkeet; Singh, K. P. (Journal of Information and Knowledge, 2018)
This study examines users’ perceptions of Web 2.0 Technologies in the Indian Institutes of Managements (IIMs) in India. Survey approach was adopted for collection of data from students, researchers and information professionals. It was found that the young respondents are active users of Web 2.0 in their personal as well as academic lives. Facebook, LinkedIn, Skype and YouTube are prominent social networks that have profoundly influenced the respondents. These technologies have been used largely to acquire useful and up-to-date information pertaining to academic and research work and for socializing.